THE INFLUENCE OF INTEGRATED AND SEPARATE TRAINING ON STUDENTS’ META-AFFECTIVE DURING SCIENCE LEARNING - Lilit Rusyati; Nuryani Y. Rustaman; Ari Widodo; Minsu Ha (Jurnal Pengajaran MIPA, 2022)
Affective dimension is one that must be assessed. Unfortunately, there is no learning that teaches students specifically how to recognize and control affective. Therefore, this study provides training to students on meta-affective strategies during science learning. The Static-group pretest-posttest design was chosen as the research method because it compares integrated training (facilitated by the teacher) and separate training (independent by students). MATS (Meta-Affective Trait Scale) questionnaire was adapted by adding 34 statements so that the total number is 51 statements. There were two experimental groups, each consisting of 50 students. Statistical tests show that there is no difference in students' meta-affective in integrated training and separate training. However, analysis per statement showed that separate training were better at recognizing and regulating meta-affective. In addition, in both integrated training and separate training, it is equally difficult to reduce negative emotions. This result implies that science learning should also focus on the affective and teacher should not give negative labels to students.